Investigation of polyamide 12 isothermal crystallization through the application of the phase-field model - Teo, Benjamin How Wei (2023)
Crystallization of polyamide 12 (PA12) is an essential process requiring thorough investigation for evaluating the mechanical properties after the polymer parts are manufactured. The change in crystallization temperature results in different crystallization behaviors for PA12. Hence, the crystal morphology of PA12 achieved provides important information about crystallization behavior, especially for those produced through additive manufacturing due to its heterogenous cooling rate in a single print bed. Considering the need of investigating PA12 crystallization using phase-field modeling, this paper aims to simulate the spherulite morphology of PA12 undergoing isothermal crystallization. This model is compared with the spherulite morphologies obtained from the optical microscopy test. The model shows that PA12 spherulites have thicker dendrites when the isothermal temperature is higher. The present phase-field model can determine the spherulite morphologies of bulk printed PA12 based on the crystallization condition and be used to evaluate the properties of the printed part.